2021
DOI: 10.1002/ppul.25291
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric obstructive sleep apnea—Dental professionals can play a crucial role

Abstract: The significant contribution of dental professionals to the management of selected adult obstructive sleep apnea (OSA) cases is understood. Among children, it has also been suggested that dental professionals may also help screen and manage this morbidity in selected cases. It has also been noted that our understanding of pediatric OSA lags significantly behind adult OSA. During the screening process for potential pediatric OSA cases, dental professionals may be quite helpful as specific craniofacial abnormali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 66 publications
(156 reference statements)
0
35
0
3
Order By: Relevance
“…[50][51][52][53] Some studies have found a positive association between SDB symptoms and mandibular retrognathia, steep mandibular plane, and convex facial profile. 26,50,53,60 Previous studies have found that upper airway dimensions are smaller in children with large skeletal overjet and mandibular retrognathia, which might predispose to SDB. [37][38][39]62 The association between mandibular retrognathia and SDB is in agreement with the included study by Ikävalko et al 2018 but not with Ikävalko et al 2012.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[50][51][52][53] Some studies have found a positive association between SDB symptoms and mandibular retrognathia, steep mandibular plane, and convex facial profile. 26,50,53,60 Previous studies have found that upper airway dimensions are smaller in children with large skeletal overjet and mandibular retrognathia, which might predispose to SDB. [37][38][39]62 The association between mandibular retrognathia and SDB is in agreement with the included study by Ikävalko et al 2018 but not with Ikävalko et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…65 It has previously been found that the craniofacial morphology is associated with the dimensions of the upper airway due to an extended head posture including morphological deviations of the upper spine and low tongue position. 26,[66][67][68] These factors and certain craniofacial morphological deviations like mandibular retrognathia are factors related to SDB. 26,36,66,67 Horizontal maxillary overjet is not always seen in children with mandibular retrognathia due to the dentoalveolar mechanism, 65 which indicates that the underlying craniofacial morphology is important in the discussion regarding association between malocclusion and SDB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As cephalometry is routinely performed in orthodontic practice, orthodontists are strongly recommended to screen their patients for sleep breathing disorders and AH in clinical practice [35]. Children with suspected AH based on lateral cephalograms could be referred by orthodontists to the ENT department for diagnosis and treatment [9].…”
Section: Discussionmentioning
confidence: 99%
“…Children with AH usually present in orthodontics department with malocclusion, thus the routine screening of AH in dental practice is helpful for preventing relevant craniofacial and systemic consequences [9]. Nasal endoscopy stands as the current gold standard of diagnosing AH [10].…”
Section: Introductionmentioning
confidence: 99%